(untitled) (Ogigia. Revista Electrónica de Estudios Hispánicos, 2020)
This paper examines the semantic range of the term klug (clever, wise, intelligent) in Grimm’s Fairy Tales, in particular in Die Kluge Else. With the analysis we propose a Spanish translation of the term. If tales valuate positively the character (it succeeds in performing an action), klug is related to terms like shrewdness, sagacity; if they show a negative character (it fails to perform an action), meanings are related to foresight, wisdom, reflection.